The Creative Process and Melodic Structure Analysis of Mahalini's Song Sial, Mawang's Version - Farika Nur Damayanti - (Repertoar, 2026)
This study aims to describe Mawang's creative process in arranging the song "Sial" and to analyze its melodic structure.  The research used qualitative methods, including observation, online interviews via WhatsApp video calls, and document analysis.  Mawang took a creative approach by listening to the original version of the song in depth and developing musical ideas spontaneously, without altering its structure, arrangement, or musical elements, as a form of respect for Mahalini's work.  The production process involved simultaneous recording of vocals and instruments, followed by mixing and mastering.  The song's melodic structure consists of Verse I, Pre-Chorus, Chorus, Verse II, Pre-Chorus, Chorus, Bridge, and Coda.  Analysis of the melodic motifs reveals four in the Verse section, two in the Pre-Chorus, five in the Chorus, four in the Bridge, and five in the Coda.  These motifs involve literal repetition techniques, ascending and descending sequences, and augmentation.  This study shows that the creative process is an important medium for developing ideas for unique and diverse arrangements.